Horae lyricae: poems, chiefly of the lyric kind ... - Watts, Isaac (Benson collection of hymnals and hymnology, 1779)
Book I. To devotion and piety. -- Book II. To virtue, honour, and friendship. -- Book III. To the memory of the dead.